A Finite Element Model of the Proximal Sesamoid Bones of the Horse Under Different Loading Conditions - Thompson, K. N.; Cheung, T. K. (Veterinary and Comparative Orthopaedics and Traumatology, 1994)
Fracture of the proximal sesamoid bones is a common injury of racing horses, usually resulting from over-dorsiflexion of the metacarpophalangeal joint. The purpose of this study was to develop a computer-aided method utilizing stereo-radiography, computed tomography, and finite element method to determine three-dimensional stress distribution in the proximal sesamoid bones during metacarpophalangeal joint dorsiflexion. The stress pattern was characterized by a compressive component on the articular part of the bone and a tensile component on the non-articular part of the bone. Maximum principal stresses were 2.5, 9.1 and 15.5 MPa and minimum principal stresses were -1.9, -9. 2 and -14. 9 MPa for metacarpophalangeal joint angles of 140°, 125° and 110°, respectively. The distal portion of the articular part of the bone experienced the largest compressive stress. In this study changes in the orientation and magnitude of the ligament force vectors did not significantly change stress patterns of the proximal sesamoid bone.This study was designed to determine stress patterns of the proximal sesamoid bones in horses. Stress patterns were determined by finite element method analysis. Compressive stresses were present on the articular side, and tensile stresses were present on the nonarticular side of the bones. The magnitude of load applied to the bone did not appreciably change the pattern of stresses.
Keywords: Sesamoid bones; equine orthopaedic disease; equine leg